USING MEANING-FOCUSED OUTPUT STRAND IN DIALOGIC MEANING CONSTRUCTION OF SEASPEAK - Wardani, Henny Wahyu (Universitas Negeri Semarang, 2010)
This paper attempts to describe features of Seaspeak and suggests a way of teaching this specific kind ofcommunication to learners by using a strategy which is called meaning-focused output strand thatincorporates the productive skills of writing and speaking. This strategy is intended to raise learners’ formawareness typical of seaspeak which has a set of constrains of language use of closed register distinctivefrom that of daily communication. Seaspeak is transactional in nature, involving intership and intrashipcommunication. Intership communication involves a vessel’s OOW and VTS when the ship is about to berth,cast off, load or discharge. Learners at Politeknik Ilmu Pelayaran need to be well-equipped with how tosuccessfully deal with such a communication encountered later as seafarers. One way of achieving this isby having them actively involved in a diologic meaning construction with their peers an a collaborativemanner. Meaning focused output strand provides them with activities that enable them to benefit from thefeedback and correction they get during the join construction of a maritime discourse from their fellowlearners.